Awareness, Knowledge and Perception of the Career Prospects in Optometry Among Optometry Students in Nigeria - Odjimogho, Stella E.; Enodolomwanyi, Deborah O.; Odjimogho, Emoefe S. (Kwaghe International Journal of Sciences and Technology, 2025)
Optometry practice is an essential aspect of health care system, that examine, diagnose, treat and manage diseases and disorders of the visual system and related systemic conditions. It requires specialty training to provide quality healthcare for people with visual disorders. This study assessed the level of awareness, knowledge and perception of the Career prospects among optometry students in Nigeria. A total of 437 respondents participated in this study comprising of 254 (58.1%) females and 183 (41.9%) males and their mean age was 23.4±2.2. Two hundred and forty-seven (247) representing (56.52%) of the study population, had good level of awareness and 330 (75.51%) had good level of knowledge of the career prospects in optometry. In conclusion, there is a low level of good awareness and high level of good knowledge of the career prospects in optometry among optometry students in Nigeria.